A review of the peripheral proprioceptive apparatus in the larynx - Hernández-Morato, Ignacio; Yu, Victoria X.; Pitman, Michael J. (Frontiers in Neuroanatomy, 2023)
The larynx is an organ of the upper airway that participates in breathing, glutition, voice production, and airway protection. These complex functions depend on vocal fold (VF) movement, facilitated in turn by the action of the intrinsic laryngeal muscles (ILM). The necessary precise and near-instantaneous modulation of each ILM contraction relies on proprioceptive innervation of the larynx. Dysfunctional laryngeal proprioception likely contributes to disorders such as laryngeal dystonia, dysphagia, and vocal fold paresis and paralysis. While the proprioceptive system in skeletal muscle derived from somites is well described, the proprioceptive circuitry that governs head and neck structures such as VF has not been so well characterized. For over two centuries researchers have investigated the question of whether canonical proprioceptive organs, muscle spindles and Golgi tendon organs, exist in the ILM, with variable findings. The present work is a state of the art review of the peripheral component of laryngeal proprioception, including current knowledge of canonical and possible alternative proprioceptive circuitry elements in the larynx.